The Spirit Of 45 The Glove People (Value Of Multicultural Islamic Education As A Student Enterpreneur Spirit At Bahrul Maghfiroh Boarding School, Merjosari, Lowokwaru, Malang) - Mariyono, Dwi; Maskuri, Maskuri; Ghony, Muhammad Djunaidi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to analyze how to shape the entrepreneurial spirit of students through the values of multicultural Islamic education. The research method uses qualitative research with a descriptive approach. Methods of data collection using interviews, observation and documentation. We use the triangulation method to check the validity of the data. This study uses qualitative descriptive data analysis techniques by reducing data, presenting verification data and drawing conclusions. From the results of the study it was concluded that in forming the entrepreneurial spirit of students at the Bahrul Maghfiroh Islamic Boarding School, it was 1). The values of multicultural Islamic education that are instilled are four values, namely shidiq, amanah, tabligh, fathonah and five values, namely ta'aruf, tasawuth, tawazun, tasamuh, ta'awun which is called the spirit of 45. 2) The implementation process involves all pesantren elements in formal and non-formal education consisting of human elements and non-human elements in pesantren activities, learning activities, pesantren traditions, the involvement of students in running pesantren businesses and the example of kyai, ustadz/teachers. 3). The implementation model that is applied is to integrate the spirit of 45 in every activity and learning in Islamic boarding schools and the role mode of the kyai with a top down strategy to form an entrepreneurial spirit in the form of: passion: having high enthusiasm to pursue their dreams, independent being able to independently realize their dreams, opportunity creation: awareness of existence must pay attention to user or market factors, creative and innovative creative and innovative looking for opportunities and solutions in realizing their dreams.